Manajemen Rekrutmen Calon Pegawai Negeri Sipil Dalam Hubungan Dengan Kualitas Pelayanan Publik di Kota Manado - Liando, Daud Markus (JURNAL ILMIAH SOCIETY, 2016)
Poor performance of the bureaucracy is the main problem which is experienced by the Indonesian nation. In the city of Manado, one of the reasons was the poor quality of public services due to the still unrecovered civilian civil service recruitment process. Recruitment of more based on the proximity and collusion, so that the employees who were recruited not meet the standards in order to improve the quality of public services. This study uses the theory of Zeithaml, at.al. (1990: 20), states that the quality of service is determined by Tangible Dimension, Dimension ReliabilityDimensi responsivness, Assurance and Dimensions Dimensions Empathy.Bertujuan to Know What factors are affecting the management of recruitment in Manado city and aims Knowing whether the Management recruitment in Manado city can have an impact on the quality of public services This research uses descriptive method for implementation includes data, analysis and interpretation of the meaning and diperoleh.Penelitian data is structured as an inductive study that is looking for and collecting data in the field with the aim to determine the factors, form elements, and a nature of the phenomena in the society. The study says that the process of public service delivery in the city Manadobelum provide a sense of satisfaction to the community caused by the long turnaround time, quality of service result of inadequate attitude is unjust in service. The poor quality of public services in the city of Manado due to the lack of competence of the employees, the rate inadequate skills and behaviors of employees who buruk.Disamping the quality of public services has not been due to the limited number of staff and infrastructure services employees who do not yet memadai.Rekrutmen dipersipakan well be wrong the triggers of poor public services. To fix the quality of public services in the city of Manado, the management of recruitment civil servant in the city of Manado should dibenahi.Syarat appointment CPNS expected to not only pay attention to the cognitive ability or knowledge, but the most important is attention to emotional factors / character and skills. Keywords: Management, recruitment, quality, service, public